Commodifying communism : - Wank, David L. (Cambridge University Press, 1999)
Commodifying Communism is an ethnographic study of the role of personal ties between private entrepreneurs and local officials in the organization of China's emerging market economy. It is based on almost two years of fieldwork in Xiamen City, Fujian, one of China's five special economic zones. A close examination of how private business is conducted through these ties sheds light on the dynamism of China's market economy and its political consequences